Fetal colon cell line FHC exhibits tumorigenic phenotype, complex karyotype, and TP53 gene mutation - Soucek, Karel; Gajdusková, Pavla; Brázdová, Marie; Hýzd'alová, Martina; Kocí, Lenka; Vydra, David; Trojanec, Radek; Pernicová, Zuzana; Lentvorská, Lenka; Hajdúch, Marián; Hofmanová, Jirina; Kozubík, Alois (Cancer genetics and cytogenetics, 2010)
Stable cell lines obtained by spontaneous immortalization might represent early stages of malignant transformation and be useful experimental models for studies of mechanisms of cancer development. The FHC (fetal human cells) cell line has been established from normal fetal colonic mucosa. Detailed characterization of this cell line and mechanism of spontaneously acquired immortality have not been described yet. Therefore, we characterized the FHC cell line in terms of its tumorigenicity, cytogenetics, and TP53 gene mutation analysis. FHC cells displayed capability for anchorage-independent growth in semisolid media in vitro and formed solid tumors after transplantation into SCID (severe combined immunodeficiency) mice. This tumorigenic phenotype was associated with hypotriploidy and chromosome number ranging from 66 to 69. Results of comparative genetic hybridization arrays showed that most chromosomes included regions of copy number gains or losses. Region 8q23 approximately 8q24.3 (containing, e.g., MYC proto-oncogene) was present in more than 20 copies per nucleus. Moreover, we identified mutation of TP53 gene in codon 273; triplet CGT coding Arg was changed to CAG coding His. Expression of Pro codon 72 polymorphic variant of p53 was also detected. Mutation of TP53 gene was associated with abolished induction of p21(Waf1/Cip1) and MDM-2 proteins and resistance to apoptosis after genotoxic treatment. Because of their origin from normal fetal colon and their relative resistance to the induction of apoptosis, FHC cells can be considered a valuable experimental model for various studies.
Keywords: buňky - růstové procesy; signální transdukce; DNA Damage; karcinoembryonální antigen; Cell Growth Processes; Cell Adhesion; apoptóza; srovnávací genomová hybridizace; transformované buněčné linie; hybridizace in situ fluorescenční; Neoplasm Transplantation; Cell Line, Transformed; Keratins; poškození DNA; DNA Mutational Analysis; Mice, SCID; plod; karyotypizace; protoonkogen Mas; Signal Transduction; HCT116 buňky; Comparative Genomic Hybridization; Mice; Proto-Oncogene Mas; mutační analýza DNA; fenotyp; cytogenetické vyšetření; HCT116 Cells; Karyotyping; In Situ Hybridization, Fluorescence; Colon; nádory tračníku; keratiny; Phenotype; ženské pohlaví; zvířata; Humans; transplantace nádorů; kolon; Carcinoembryonic Antigen; Colonic Neoplasms; Genes, p53; myši; nádorová transformace buněk; buněčná adheze; Fetus; myši SCID; Female; Cell Transformation, Neoplastic; geny p53; lidé; Cytogenetic Analysis; Apoptosis; Animals